Effects of salicylate derivatives on localization of p.H723R allele product of SLC26A4. Issue 6 (December 2022) - Murakoshi, Michio; Koike, Yuhi; Koyama, Shin; Usami, Shinichi; Kamiya, Kazusaku; Ikeda, Katsuhisa; Haga, Yoichi; Tsumoto, Kohei; Nakamura, Hiroyuki; Hirasawa, Noriyasu; Ishihara, Kenji; Wada, Hiroshi
Abstract: Objective: Pendrin is a transmembrane protein encoded by the SLC26A4 gene that functions in maintaining ion concentrations in the endolymph of the inner ear, most likely by acting as a chloride/bicarbonate transporter. Variants in the SLC26A4 gene are responsible for sensorineural hearing loss. Although pendrin localizes to the plasma membrane, we previously identified that 8 missense allele products of SLC26A4 were retained in the intracellular region and lost their anion exchange function. We also found that 10 mM salicylate induced the translocation of 4 out of 8 allele products from the intracellular region to the plasma membrane and restored their anion exchanger activity. However, since 10 mM salicylate exhibits cytotoxicity, the use of chemical compounds with less cell toxicity is needed. In the present study, therefore, salicylate derivatives were used as the chemical compounds and their effects on the p.H723R allele products of SLC26A4 were investigated. Methods: HEK293 cells were transfected with the cDNA of p.H723R. Cell proliferation, viability and toxicity assays were performed to investigate the response and health of cells in culture after treatment with four types of salicylate derivatives, i.e., 2-hydroxybenzyl alcohol, 2, 3-dihydroxybenzoic acid, 2'-hydroxyacetophenone and methyl salicylate. The effects of these salicylate derivatives on the localization of the p.H723R were investigated by immunofluorescence microscopy. Results: The application of 10 mM salicylate showed an increase in cell toxicity and decrease in cell viability, leading to a significant decrease in cell proliferation. In contrast, the application of 1 mM salicylate derivatives did not show any significant increase in cell toxicity and decrease in cell viability, corresponding to a logarithmic increase in cell concentration with an increase in culture time. Immunofluorescence experiments showed that the p.H723R retained in the endoplasmic reticulum (ER). Among the salicylate derivatives applied, 2-hydroxybenzyl alcohol induced the translocation of p.H723R from the ER to the plasma membrane 3 h after its application. Conclusion: The results obtained showed that 2-hydroxybenzyl alcohol restored the localization of the p.H723R allele products of SLC26A4 from the ER to the plasma membrane at a concentration of 1 mM by 3 h after its administration with less cytotoxicity than 10 mM salicylate.